Perbedaan Manajemen Konflik pada Atlet Taekwondo Laki-Laki dan Perempuan di Kota Ternate - Muhammad Reza Kaosar; Mustaqim Setiyo Ariyanto; Komarudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
One of the common problems that occurs in Indonesia regarding conflict management in Taekwondo, is leadership conflict in Taekwondo organizations. In addition, general problems that occur in Indonesia regarding conflict management include educational problems, such as limited access to education, educational inequality, teacher quality, and curriculum that is considered irrelevant. Social problems can also trigger conflict, such as power struggles in political and economic contexts. Social conflict is also a serious concern, with the number of social conflicts in Indonesia tending to increase from year to year. Therefore, conflict management in Indonesia needs to pay attention to various aspects, ranging from education, social problems, to political and economic dynamics. Research Objective: This research is to determine the understanding or description of the differences in conflict management among male and female taekwondo athletes in Ternate City. Method: This research uses a questionnaire as a data collection tool. A questionnaire/questionnaire is a data collection method that has been carried out by asking several types of questions related to the research problem. One of the common problems that occurs in Indonesia regarding conflict management in Taekwondo, is leadership conflict in Taekwondo organizations. In addition, general problems that occur in Indonesia regarding conflict management include educational problems, such as limited access to education, educational inequality, teacher quality, and curriculum that is considered irrelevant. Social problems can also trigger conflict, such as power struggles in political and economic contexts. Social conflict is also a serious concern, with the number of social conflicts in Indonesia tending to increase from year to year. Therefore, conflict management in Indonesia needs to pay attention to various aspects, ranging from education, social problems, to political and economic dynamics. Research Objective: This research is to determine the understanding or description of the differences in conflict management among male and female taekwondo athletes in Ternate City. Method: This research uses a questionnaire as a data collection tool. A questionnaire/questionnaire is a data collection method that has been carried out by asking several types of questions related to the research problem.